Formation of Mono-Organismal and Mixed Staphylococcus aureus and Streptococcus mutans Biofilms in the Presence of NaCl - Yusuke Iwabuchi; Hiroko Yoshida; Shuichiro Kamei; Toshiki Uematsu; Masanori Saito; Hidenobu Senpuku (Microorganisms)
Staphylococcus aureus, an opportunistic bacterium found in the oral cavity, has been reported as a causative agent of infective endocarditis and pneumonia. Salt is an essential mineral for cell maintenance in the human body. This study was conducted to clarify how salt affects the formation of biofilms by S. aureus and Streptococcus mutans, pathogens implicated in dental caries. Bacteria were cultivated with various concentrations of NaCl on a 96-well microtiter plate in tryptic soy broth with 0.25% sucrose or 0.25% glucose (TSBs and TSBg, respectively) for 16 h. The effects of glucosyltransferase in S. mutans membrane vesicles (MVs) and extracellular DNA during biofilm formation were also analyzed. S. aureus biofilms were induced by 0.004–0.25 M NaCl but not by NaCl at concentrations greater than 0.25 M in TSBs. The mixed S. aureus and S. mutans biofilms gradually grew and were constructed by dead cells in a NaCl concentration-dependent manner in both TSBs and TSBg. Moreover, biofilms were slightly induced by glucan generation mediated by the glucosyltransferases in MVs under high-salinity conditions. The formation of mixed-species S. aureus and S. mutans biofilms increased in the presence of both extracellular DNA and MVs. Therefore, extracellular DNA, MVs, and dead cells are factors that promote S. aureus biofilm formation under harsh conditions containing NaCl. The sugar (sucrose and glucose) ingestion-induced S. mutans biofilm may be a risk factor for infection by opportunistic pathogens such as S. aureus in individuals who consume food and drinks containing high concentrations of salt.